Getting on the bus. - Subramanian, Ajantha (Yemaya : ICSF'S Newsletter on Gender and Fisheries)
Bordering the Indian Ocean, Kanyakumari is peninsular India's southwesternmost district. Here, through years of struggle, women fishers have managed to significantly expand their citizenship rights.